Como os fatores bióticos e abióticos influenciam a distribuição dos parasitos de peixes. - Ribeiro, Thamy Santos (2016)
For parasites to optimize their distribution, they must distinguish variations in their hosts (immediate environment) and in their ecosystems (the host habitat). The investigation of the distribution of the parasites is influenced by the functional character of the hosts and the abiotic variations, represented by the different environments where the host-parasite interactions were observed. For this, data on fish-parasite relationships were obtained through field research and literature reviews in the upper Paraná River floodplain and the basin of the Amazon River. It was also calculated the Functional Diversity (FD) values of the hosts and the Taxonomic Diversity (TD) of the parasites and hosts, possibly spatial decomposition of these indices to demonstrate the ecosystem variation in species distribution. Using Generalized Linear Models (GLMS) it was observed that the parasites are sensitive enough to respond to changes in both functional characteristics of the fish and the abiotic characteristics of each ecosystem. It was observed that the multi-faceted decomposition of diversity indices is an appropriate tool for the study of macroecological patterns of parasite-host interaction, both in the immediate and ecosystem scales. Insert the DF, as well as data to analyze the functional traits, expands the knowledge about the ecological relationships that are established between the parasites and their definitive and intermediate hosts. Thus, the application of this approach in different parasitic groups would help to understand the environmental awareness of each taxon.